Electronic screening and brief intervention for unhealthy alcohol use in primary care waiting rooms – A pilot project. Issue 3 (2nd July 2020) - Bertholet, Nicolas; Cunningham, John A.; Adam, Angéline; McNeely, Jennifer; Daeppen, Jean-Bernard
Abstract: Background: In primary care, electronic self-administered screening and brief interventions for unhealthy alcohol may overcome some of the implementation barriers of face-to-face intervention. We developed an anonymous electronic self-administered screening brief intervention device for unhealthy alcohol use and assessed its feasibility and acceptability in primary care practice waiting rooms. Two modes of delivery were compared: with or without the presence of a research assistant (RA) to make patients aware of the device's presence and help users. Using the device was optional. Methods: The devices were placed in 10 participating primary care practices waiting rooms for 6 weeks, and were accessible on a voluntary basis. Number of appointments by each practice during the course of the study was recorded. Access to the electronic brief intervention was voluntary among those who screened positive. Screening and brief intervention rates and characteristics of users were compared across the modes of delivery. Results: During the study, there were 7270 appointments and 1511 individuals used the device (20.8%). Mean age of users was 45.3 (19.5), and 57.9% screened positive for unhealthy alcohol use. Of them, 53.8% accessed the brief intervention content. The presence of the RA had a major impact on the device's usage (59.6% vs 17.4% when absent). When the RA was present, participants were less likely to screen positive (49.4% vs 60.7%, P  = 0.0003) but more likely to access the intervention (62.7% vs 51.4%, P  = 0.009). Results from the satisfaction survey indicated that users found the device easy to use (93.5%), questions useful (89–95%) and 77.2% reported that their friends would be willing to use it. Conclusions: This pilot project indicates that the implementation of an electronic screening and brief intervention device for unhealthy alcohol is feasible and acceptable in primary care practices but that, without human support, its use is rather limited.